The external agent, an approach to the training of trainers in the Escuela Normal of Villavicencio (Orinoquia, 2018)
This article presents the results of a recent investigation that took the systematization of experiences as epistemological and methodological basis. In coherence with the methodology, the presence of external agent allowed to understand the experience from the pluralism and objectivity of the narratives that eviscerate and build the reality of educational phenomenon: “classroom project” in the Escuela Normal Superior of Villavicencio. The foreign agent is the catalytic converter of narrated stories and helps to understand the experience, being the “judge” and “observer” from a non-participating position.metodoAsconclusions it was found that the foreign agent is situated in two dimensions: it affects and is affected. Its presence, its action and its participation serve as external experience, as an invited expert that when it is an observer and listener it finds an alternate picture of the reality of the lives of the actors involved in the systematization; situation that promotes other dynamics of understanding of reality for the reconfiguration of the experience. In the same way, the relationship with the actions and narratives of the protagonists are doing for the external agent to place other mental realities in its perspective and recreate the experience.
Keywords: External agent; class project; systematization of experiences and narratives